Pseudo-placentational Endometrial Hyperplasia in Young Beagle Bitch - Liu, Bo; Hu, Minhua; Liu, Lu; Chen, Dixin; Guo, Qiuping (Acta Scientiae Veterinariae, 2025)
Background: Pseudo-placentational Endometrial Hyperplasia (PEH) is a well-documented pathological condition in middle-aged to older bitches, yet its occurrence in young, sexually immature canines - particularly those utilized in preclinical toxicity studies - remains profoundly underreported. This gap in literature poses challenges for interpreting uterine lesions in juvenile laboratory Beagles. Case: A 10-month-old Beagle bitch was euthanized at the study termination age during a repeat-dose toxicity study. No clinically significant abnormalities were observed in clinical observations of this animal. The animal presented with uterine nodules (0.5-0.8 cm diameter) containing serosanguinous fluid during necropsy, initially suggestive of pyometra or pregnancy. Histopathological evaluation revealed absence of inflammation or microbial colonization, contrasting with classical pyometra, and identified complex glandular hyperplasia with placental mimicry, including villous projections lined by cuboidal-to-columnar epithelium. Immunohistochemistry demonstrated epithelial-mesenchymal transition-like features, with strong vimentin expression in mesenchymal-like stromal cells and pan-cytokeratin positivity in epithelial components, while desmin and estrogen receptor alpha remained negative. Histopathological examination and immunohistochemical analysis showed Pseudo-placentational Endometrial Hyperplasia. Discussion: PEH of Beagle dog is extremely rare in the young Beagle dog. A 100 years ago, PHE has been already described in standard textbooks, and it was not wildly recognized by diagnostic pathology. Previously, it was also known as “deciduoma”. The deciduoma of uterine have been found in human, monkeys, dogs, rabbits, and rats. However, it is generally accepted that deciduoma is a neoplastic lesion. As its form of endometrial hyperplasia is similar to the normal histology of the endometrium at placentation sites in normal pregnancy, until 2008, D.H. Schlafer 1st named PEH. The present case describes the morphological and immunohistochemical features of the uterine discovered a 10-month-old Beagle bitch in toxicity and pharmacological study. During the gross examination, nodules with fluid discharge were detected in the uterus, initially prompting suspicion of pyometra or pregnancy. Given that the bitch was housed exclusively with individuals of the same sex, mating was ruled out. Histopathological analysis revealed the absence of discernible inflammation in the uterine tissue; however, structures resembling placental tissue were observed. These findings suggest endometrial hyperplasia mimicking placental morphology due to unknown etiology. Additionally, Vimentin and Pan cytokeratin exhibited strong positive expression in the areas of villous proliferation, suggesting epithelial cells in this region possess the ability to differentiate into mesenchymal tissue. Currently, the etiology of canine PEH remains unclear. It is widely believed that bacteria, foreign bodies, and other factors may contribute to PEH. While PEH may be incidentally discovered and spontaneously regress without intervention, persistent lesions warrant consideration for surgical intervention. In toxicity and pharmacological studies, PEH of the uterus has only been reported in rats. Although Beagle dog is frequently used in toxicity and pharmacological studies, respectively, historical control date for PEH in young Beagle dog has not been reported. So, our case might provide valuable information as a historical for Beagle dog. Keywords: Beagle dog, Deciduoma, PEH, pseudo-placentational endometrial hyperplasia, uterine lesions.